State regulation of competitive relations in Ukraine - Шишка, Роман Богданович; Джумагельдієва, Гульнара Джумадурдіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The scientific review of a monograph of N. M. Korchak "State regulation of competitive relations in Ukraine (economic-legal aspect)"